UPAYA MENINGKATKAN HASIL BELAJAR SISWA DALAM PENGGUNAAN METODE MIND MAP PADA PEMBELAJARAN BAHASA INDONESIA TENTANG TEKNOLOGI (Kelas IV SD Negeri Kemantran 01 ) - Andriarsih, Lyswidia (Sasando, 2018)
Using this type of research is an action research (action research), because the research carried out to solve the problem of learning in the classroom. The study also included a descriptive study, because mengmultimediakan how an applied learning and what is desired can be achieved. Based on data mastery learning outcomes of fourth grade students learning technology development that meets the KKM only four students , while students who do not meet the KKM many as 19 students . In the first cycle of students who meet the KKM as many as 16 students who meet KKM 7 students . While on the second cycle students yng meet KKM 20 students and who have not met the KKM as many as three student.